Historical approaches to integral education in Brazil - Figueiredo, Jacqueline de Sousa Batista; Aguilar, Luis Enrique (Seven Editora, 2023)
This article is a theoretical review of integral education in the libertarian, authoritarian, liberal and liberating sense, which allows us to reach the course of these conceptions to better understand their dimension and reflections in the 20th century in the history of Brazilian education, and 21st century - contemporary Brazil - on the agenda of public policies for basic education with Integral Education. Proposals that, in summary, constitute instruments in the fight against school failure, aiming at social integration. The results reveal that they are conceptions that produced theories and practices for education in an integral perspective. These theoretical currents think about integral formation in peculiar ways with the intention of developing the global formation of the individual. Sometimes the term is associated with full-time, sometimes with social training, sometimes with integral/social protection. Each of the integral education proposals presented here defined the school according to its vision of education, with its symbols and values. We believe that integral education needs more in depth investigations on the procedures and strategies used in federal government programs in order to contemplate the ambiguities, contradictions, needs and problems that Brazilian public schools present today. DOI:https://doi.org/10.56238/ptoketheeducati-005